Sosyal Hizmete Giriş - Toğa, Halim; Türk, Ahmet; Öngören, Bülent; Beki, Abdulhakim; Bal, Gürcan; Çamur, Gülsüm; Tekgöz Obuz, Aysel; Yalçın, Melike; Çetinkaya Büyükbodur, Ayşin; Karadağ, Ferda; Purutçuoğlu, Eda; Kaya, Salim; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-